Interim Protection in the European Union Courts and Lithuanian Administrative Courts - Povylius, Kristijonas (Teisė, 2025)
This paper compares the institution of interim protection in the European Union (EU) law and the administrative procedure law of the Republic of Lithuania with the objective to assess whether the Lithuanian legislation in this area complies with the EU law. The analysis finds that Lithuania’s legal framework is largely aligned with the EU law, with a few potential exceptions. Specifically, the Lithuanian law imposes greater restrictions on the types of interim measures available, as it does not permit positive interim measures or those against certain administrative acts related to financial stability and the soundness of banks. Additionally, while there exist further differences between the EU and Lithuanian law on interim protection, these do not necessarily indicate non-compliance but could serve as an inspiration for future legislative or judicial developments.
Keywords: interim protection; interim measures; provisional measures; interim relief; effective judicial protection